Evolution of Pumping and Piezometry of the Carboniferous Aquifers, Western Border of Aïr Massif: Case of the Tarat Aquifer in the Arlit Sector - Illias, Alhassane; Sani, Abdou Babaye Maman; Souleymane, Issa M. Salmanou; Boureima, Ousmane (Global Journal of Earth Science and Engineering, 2021)
The Tarat aquifer provides drinking water for the population of the city of Arlit and also provides water to industries. The exploitation of this aquifer has considerably increased in recent years. The main objective of this study is to contribute to a better understanding of the functioning of the Tarat aquifer. Thus, a methodological approach focusing mainly on the piezometric study and the analysis of evolution and estimation of the volumes of water pumped, since its development from 1969 to 2012, which has resulted in highlighting not only a general decline in the level of the Tarat aquifer, but also the piezometer level (Arli_182), reacts strongly to the solicitations of the aquifer. On this same piezometer, the water table was lowered by 30 m from 1980 to 2006 (26 years), so a drawdown of 0.86 /year.